(untitled) (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the effect of providing ergonomic exercises on reducing dysmenorrhea pain in women of childbearing age. The method used is a one-group pre-test and post-test design. The Paired T-Test research showed a result of 3.179 with a P-value of 0.000 < (0.05). In conclusion, there is an influence of ergonomic exercise on reducing dysmenorrhea pain in women of childbearing age. Keywords: Dysmenorrhea Pain, Ergonomic Exercises, Women of Childbearing Age